DESIGNING A FINANCIAL STRATEGY TO ACHIEVE BUSINESS SUSTAINABILITY - Wulandari Wulandari; Muhammad Masykur Abdillah; Rina Apriliani (Adisam Publisher, 2024)
This research aims to formulate financial strategies that support business sustainability amidst increasing demands for companies to operate environmentally and socially responsibly. The research method carried out by researchers is literature. The research results show that sustainable finance strategies depend on accurate risk assessments, efficient resource allocation, and a commitment to transparency and accountability. Effective companies adopt a triple-bottom-line approach, considering the economic, environmental, and social impacts of their business activities. Investments in green technology, energy diversification, and waste reduction initiatives have been proven to increase efficiency and reduce operational costs.